Biblical Guidelines for Educational Systems - Shakir Mamatalievich Urishov (Peerian Journals Publishing, 2023)
The Bible serves as a moral compass for many people and guides them in various areas of life. Although it does not provide specific guidelines for the modern education system, it contains principles that can be applied to educational pathways. This article examines the Bible's view of education and highlights the key principles that inspire and shape our approach to learning
Keywords: critical thinking; honesty; integrity; kindness; compassion